Energy allocation strategy during the reproductive cycle of Patagonian grouper (Acanthistius patachonicus) from the southwestern Atlantic Ocean - Sofía López; María I. Militelli; Cecilia M. Riestra; Gustavo J. Macchi (Marine and Fishery Sciences)
The term ‘condition’ is used to describe the overall health status of an animal and to describe its energy reserves. The storage and use of energy reserves are fundamental components of a species’ life strategy, and these processes directly influence the balance between current and future reproductive success. Understanding the energy allocation strategy adopted by a species is an important aspect in assessing possible variations in reproductive potential. The aim of this work was to analyse the seasonal variations of condition indices, biochemical composition, and energy density of different tissues in order to determine the strategy of energy allocation during the reproductive cycle of females Acanthistius patachonicus. Mature females were collected between April 2016 and March 2017 from commercial landings. Biochemical components such as lipids, proteins, and water content were measured in liver, gonad and muscle. The gonadosomatic index was highest during winter, at the beginning of the reproductive period, while the hepatosomatic index and condition factor did not differ among seasons. The study of the proximal composition of tissues revealed that the liver was the primary source of energy reserves. Highest values of these reserves in the liver were found before the onset of gonadal maturation (autumn). As the reproductive period progresses (winter and spring), these energy reserves decreased significantly, suggesting they were mobilized to support reproductive processes. This suggests that A. patachonicus primarily adopts a capital breeding strategy, but females possibly incorporate energy by feeding during the spawning period.